2006
DOI: 10.1021/ja061303h
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Evidence of PtSn Alloy Efficiency for CO Oxidation

Abstract: The efficiency of PtSn alloy surfaces toward CO oxidation is demonstrated from first-principles theory. Oxidation kinetics based on atomistic density-functional theory calculations shows that the Pt3Sn surface alloy exhibits a promising catalytic activity for fuel cells. At room temperature, the corresponding rate outstrips the activity of Pt(111) by several orders of magnitude. According to the oxidation pathways, the activation barriers are actually lower on Pt3Sn(111) and Pt3Sn/Pt(111) surfaces than on Pt(1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
111
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(127 citation statements)
references
References 58 publications
15
111
0
1
Order By: Relevance
“…Therefore, the evolution of the activation barrier primarily follows the variation of the interaction energy DE int between the CO molecule and the oxygen atom. This is in good agreement with the results of Dupont et al, [50] who found that the variation of the activation energy primarily follows the variation of the interaction energy between CO and oxygen atom fragments.…”
Section: Comparison Of Co Oxidation On Ib Group Metal and Metal Oxidesupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, the evolution of the activation barrier primarily follows the variation of the interaction energy DE int between the CO molecule and the oxygen atom. This is in good agreement with the results of Dupont et al, [50] who found that the variation of the activation energy primarily follows the variation of the interaction energy between CO and oxygen atom fragments.…”
Section: Comparison Of Co Oxidation On Ib Group Metal and Metal Oxidesupporting
confidence: 93%
“…A convenient way to interpret the stability of the TS has been introduced originally by Hammer for NO dissociation on metal surfaces [49] and later used by Dupont et al [50] to explain the CO oxidation process. The formula for adsorption energy at the TS is derived as follows [Eq.…”
Section: Comparison Of Co Oxidation On Ib Group Metal and Metal Oxidementioning
confidence: 99%
“…[4][5][6] The latter is key to more CO-tolerant catalysts for the anodes of reformate fuelled H 2 PEM fuel cells and direct alcohol fuel cells. Fundamental studies have shown that CO oxidation occurs at reduced overpotential at Sn and SnO 2 (or its hydrated form) modied Pt 7-10 and at Pt 3 Sn 11-14 compared to Pt electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…The role of Mo in CO electro-oxidation, however, remains elusive. Like in the case of PtSn and PtNi catalysts, 12,26,27 one cannot completely exclude a possibility that the modulation of electronic structure induced by Mo could have an effect on the interaction of Pt and CO, which also dictates the catalytic activity. To elucidate the alloying effect on the adsorption strength of CO, we investigated the role of Mo in CO electro-oxidation using X-ray absorption spectroscopy, and our results are discussed.…”
Section: Introductionmentioning
confidence: 99%